Antibacterial power effectiveness of calcium hydroxide and propolis mixture on Fusobacterium nucleatum bacteria - ira Widjiastuti; S. Sukaton; Agnes Melinda Wong; Nanik Zubaidah (Universitas Airlangga, 2019)
Background: Calcium hydroxide is a root canal dressing material that is widely used in dentistry because of its ability to regenerate hard tissue and eliminate bacteria. According to Ferreira et al. (2015), Fusobacterium nucleatum was found in 90% of teeth that had a root canal treatment done using calcium hydroxide as an intracanal medication. Due to this shortcoming of the antibacterial power of calcium hydroxide, additional research on alternative ingredients that can be combined with calcium hydroxide to improve its antibacterial power is necessary. Propolis is a natural material that has high antibacterial power and has long been used in dentistry. The addition of propolis to calcium hydroxide is expected to improve the antibacterial power of calcium hydroxide without eliminating its function in terms of regenerating hard tissue. Purpose: To find out how effective is the antibacterial power of a combination of calcium hydroxide and propolis against Fusobacterium nucleatum. Methods: The research was carried out using 4 treatment groups consisting of 6 samples for each group. Group 1 is given a combination of calcium hydroxide and propolis with a ratio of 1:1, group 2 with a ratio of 1:1.5, group 3 with a ratio of 1:2, and group 4 is a positive control of calcium hydroxide and sterile aquadest suspension. Each sample was put into a test tube containing BHIB and a suspension of Fusobacterium nucleatum, incubated at 37ºC for 24 hours, and vortexed for 1 minute. A total of 0.1 ml of bacterial inoculum was taken from each sample and then put into the MHA and grown for 24 hours. The number of Fusobacterium nucleatum colonies grown on MHA was calculated and expressed using the Colony Forming Unit (CFU). Results: There were fewer colonies of Fusobacterium nucleatum in the treatment group compared to the control group. Conclusion: The combination of calcium hydroxide and propolis has an effective antibacterial power against Fusobacterium nucleatum which the ratio of 1:2 is more effective than ratio of 1:1,5 and 1:1.